Resilience in war veterans with traumatic bran injury: review and clinical case - Assonov, Dmytro O.; Khaustova, Olena O. (Psychiatry, Neurology and Medical Psychology, 2020)
Traumatic brain injury (TBI) is a condition that negatively affect the social reintegration and restoration of adaptation mechanisms in war veterans is. The negative impact of TBI on veterans` quality of life, their social and family functioning, labor adaptation, reintegration into society can last for years. There is a need to study the factors that contribute to the successful rehabilitation of veterans with TBI and increase their effective interaction with the stressful environment, reduce the severity of symptoms. Resilience may be among these factors. The aim of this review was: (1) to systematize the information available in the scientific literature on resilience of war veterans with TBI and to outline promising areas for further research; (2) to analyze the clinical case of TBI with reduced resilience in a veteran of warfare in the area of ​​anti-terrorist operation/operation of united forces. Effective resilience in war veterans is associated with a milder TBI symptoms, fewer symptoms of PTSD, which confirms its important role in medical and psychological rehabilitation. However, the dynamic aspects of resilience as a process are currently insufficiently disclosed in the scientific literature concerning veterans of the trauma war. There is no single interpretation and approach to its psychometric study. The social components of veterans` resilience are well studied, but little attention is paid to cognitive and emotional components of resilience, despite a known decrease in the cognitive and emotional functioning of veterans after TBI. There is a need to develop resilience-oriented interventions specific to veterans. The presented clinical case complements the information available in the literature on the association of resilience with symptoms of TBI, and confirms the important role of resilience assessment in making a rehabilitation prognosis. Complementing trauma rehabilitation programs with short-term positive interventions and cognitive rehabilitation sessions can have a positive effect on trauma symptoms and resilience, probably through its cognitive and emotional components.